2022
DOI: 10.14309/ctg.0000000000000513
|View full text |Cite
|
Sign up to set email alerts
|

Risk of cervical cancer in inflammatory bowel disease: A meta-analysis of population-based studies

Abstract: INTRODUCTION: There is increased risk of several malignancies in inflammatory bowel disease (IBD). However, evidence regarding risk of cervical cancer in IBD is conflicting. We aimed to investigate the risk of cervical cancer in IBD by undertaking a systematic review and meta-analysis of unselected, population-based studies. METHODS: MEDLINE, EMBASE, and Cochrane Library were searched using Medical Subject Heading terms, and 2 reviewers independently sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…This risk is influenced by the patient's specific risk factors, such as older age and smoking, and by the concomitant use of TNFi. However, the overall incidence remains low and recent guidelines conclude that patients treated with thiopurines should adhere to the skin and cervical cancer screening programs recommended for the general population [10,28,70,100,[106][107][108][109]121,125,127].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This risk is influenced by the patient's specific risk factors, such as older age and smoking, and by the concomitant use of TNFi. However, the overall incidence remains low and recent guidelines conclude that patients treated with thiopurines should adhere to the skin and cervical cancer screening programs recommended for the general population [10,28,70,100,[106][107][108][109]121,125,127].…”
Section: Discussionmentioning
confidence: 99%
“…There is conflicting data on the risk of cervical neoplasia in women with IBD, particularly those undergoing thiopurines [28,47,70,[124][125][126]. In a recent meta-analysis of five unselected population-based studies including 74,310 patients with IBD and 2,029,087 reference patients, the authors did not show a statistically significant increased risk for cervical cancer in IBD patients under therapy with thiopurines (HR = 0.96; 95% CI, 0.60-1.50) [127]. However, a meta-analysis published in 2015 that took into account five retrospective cohort studies and three case controls studies of patients with IBD on any immunosuppression, including steroids, thiopurines, or biologic therapy, with cervical high-grade dysplasia/cancer, revealed an increased risk of cervical high-grade dysplasia (HGD) or cancer in patients with IBD on any immunosuppressive therapy and compared with population controls without IBD (OR: 1.34; 95% CI: 1.23-1.46] [125].…”
Section: Thiopurinesmentioning
confidence: 99%
“…The pathogenesis of UC is unknown and is related to a variety of factors including genetics, immunity, gut ora and environmental factorsz (El Mouzan et al 2013; Deng et al 2023;Zhou et al 2023). With the deepening of the research, it is found that the intestinal ora has a closer connection with UC, and the bene cial bacteria in the intestinal ora such as Faecalibacterium Prausnitzii, Roseburia and bacteroides can secrete short-chain fatty acids and secondary bile acids to regulate the immune system and the proliferation and development of intestinal epithelial cells to keep the intestinal mucosa intact (Mann et al 2022; Chen et al 2023), and regulate the neurotransmitters and vasoreactivity as well as energy metabolism at the same time, and further alleviate the intestinal in ammation to achieve the goal of protect the intestinal mucosa. However, when the gut ora is out of balance, it can lead to the accumulation of harmful substances, damage the intestinal mucosa, enhance the invasiveness of pathogens and exacerbate symptoms in UC patients.…”
Section: Introductionmentioning
confidence: 99%
“…These results are in contrast to the most recent meta‐analysis. Mann et al identified 5 population‐based studies, including 74,310 patients with IBD and 2,029,087 reference patients, across 5 different countries 3 . A meta‐analysis by disease subtype indicated no statistically significant increased risk in Crohn's disease (HR: 1.36; 95% CI: 0.83–2.23) or ulcerative colitis (HR: 0.95; 95% CI: 0.72–1.25) or in patients treated with thiopurines (HR: 0.96; 95% CI: 0.60–1.50).…”
mentioning
confidence: 99%